Multifunctionality of methanolic extract of Mitracarpus frigidus for antioxidant, photoprotective and anti-inflammatory activities (Research, Society and Development, 2022)
The objective of this study was to determine the flavonoid content in the methanolic extract of the aerial parts of Mitracarpus frigidus (MFM), as well as to evaluate cell viability and the antioxidant, anti-inflammatory and photoprotective potential of this extract. Flavonoid content was determined by spectrophotometer assay with aluminum chloride reagent. The antioxidant activity was evaluated by the phosphomolybdenum complex and β-carotene/linoleic acid system methods. The anti-inflammatory activity was evaluated by cell viability assays, dosage of cellular nitric oxide (NO) levels and metalloprotease (MMP) activity. The in vitro photoprotective activity was evaluated by the Mansur and COLIPA methods. The flavonoid content determined for the spectrometric method was 102.46 ± 5.66 mg/g rutin equivalent, respectively. The phosphomolybdenum assay showed 33.80% Relative Antioxidant Activity (RAA) for quercetin and 51.52% RAA for rutin, while the β-carotene/linoleic acid assay obtained 45.10 ± 1.79% inhibition at a concentration of 38.46 µg/mL. The anti-inflammatory activity showed that the extract reduced cellular NO levels and MMP-9 activity at the tested concentrations, without significantly altering MMP-2 activity. The photoprotective activity by the Mansur method obtained low SPF. By COLIPA method, the formulation containing 5% of MFM and 5% of filter obtained SPF of 8.61 ± 0.49, considered acceptable by ANVISA. The results indicate that the species M. frigidus has great potential as an antioxidant, anti-inflammatory and to compose, as an adjuvant, photoprotective formulations.